2013
DOI: 10.1021/om400892x
|View full text |Cite
|
Sign up to set email alerts
|

Borylated Tetrazoles from Cycloaddition of Azide Anions to Nitrilium Derivatives ofcloso-Decaborate Clusters

Abstract: Interaction of the closo-decaborate clusters [Bu n 4 N][B 10 H 9 (NCR)] (R = Me 1a, Et 1b, Bu t 1c, Ph 1d) with the azide [Ph 3 PNPPh 3 ]N 3 proceeds immediately upon mixing the reagents in an MeCN solution at RT, giving the borylated 1,5-disubstituted tetrazoles [B 10 H 9 (N 4 CR)] 2− in essentially quantitative yield. On a synthetic scale, sodium azide, NaN 3 , reacts similarly with the nitrile functionality of 1a−d in an acetonitrile suspension under mild conditions (RT, 15 h) to afford selectively the bory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 93 publications
0
13
0
Order By: Relevance
“…[13][14][15][16][17][18] Previously we discovered convenient method of synthesis of disubstituted oxonium derivatives using CF 3 SO 3 H as electrophilic inductor. [19] This method is quite universal and allows to produce disubstituted derivatives containing various exo-polyhedral bonds.…”
Section: Methodsmentioning
confidence: 99%
“…[13][14][15][16][17][18] Previously we discovered convenient method of synthesis of disubstituted oxonium derivatives using CF 3 SO 3 H as electrophilic inductor. [19] This method is quite universal and allows to produce disubstituted derivatives containing various exo-polyhedral bonds.…”
Section: Methodsmentioning
confidence: 99%
“…[358] Just as for the reactions of [Co III (N 3 )(chelate)L] with RCN a three-centred transition state can be ruled out on grounds of coordinative saturation. So it would appear that in both cases the initial products form directly, viz.…”
Section: Miscellaneousmentioning
confidence: 99%
“…It was previously shown that the addition of nucleophilic reagents of various natures to nitrile functional groups in anionic boron clusters can be considered as a convenient way of directed synthesis of their substituted derivatives [12][13][14][15][16][17][18][19][20][21][22][23][24], including those based on biologically active substances [6,25] and biomimetic systems [26,27]. It was found that the addition of tertbutyl esters of proteinogenic amino acids to nitrile derivatives of the closo-decaborate anion and their subsequent selective hydrolysis is a convenient method for the preparation of N-borylated peptides [28].…”
Section: Introductionmentioning
confidence: 99%